Does Qatar Face a Trade-off Between Economic Growth and CO2 Emissions? - Shannak, Sa'd; Contestabile, Marcello (Frontiers in Environmental Science, 2022)
Driven by the development of the oil and gas sector, Qatar has made remarkable economic achievements over the past few decades. However, Qatar’s high dependence on fossil fuels has resulted in a rapid increase in its CO2 emissions. As such, the country may be facing a trade-off between achieving continued economic growth and carbon emissions reductions. This study empirically analyzes the relationship between economic growth and carbon emissions in Qatar, using annual data of income and CO2 emissions from 1970 to 2018. The analysis was conducted by employing the Environmental Kuznets Curve (EKC) framework and the Decoupling Index (DI) approach. The EKC was evaluated using the Fully Modified Ordinary Least Squares cointegration method. Additionally, a robustness check was conducted by Canonical Cointegrating Regression (CCR) cointegration method to confirm the results attained by FMOLS. The findings support the evidence of an N-shaped relationship and suggest that the country is currently undergoing expanding relative decoupling. Although findings show that Qatar’s per capita emissions have been declining over the last few years, additional measures such as energy conservation, energy efficiency and renewable energy are required to allow cost-effective carbon emission reductions.